Determining Hydraulic Conductivity for Air‐Filled Porosity in an Unsaturated Frozen Soil by the Multistep Outflow Method. Issue 1 (15th February 2013) - Zhao, Ying; Nishimura, Taku; Hill, Robert; Miyazaki, Tsuyoshi
Abstract : Accurate simulation of snowmelt infiltration and runoff in frozen soil is important for many environmental and engineering issues in cold regions. It is well known that infiltration in frozen soil is dramatically reduced due to the impedance of ice crystals; however, it is very often inaccurately predicted because of limited data to parameterize the related processes. In this study, the hydraulic conductivity K ( h ) for air‐filled porosity in an unsaturated frozen soil was investigated by employing a multistep pressurized outflow method using antifreeze liquid. Comparisons of water flow in both partially frozen and unfrozen soils indicated that frozen soil significantly reduced K ( h ) due to the blocking effects of ice crystals. Based on one common K ( h )‐based hydraulic equation, an impedance parameter for liquid‐filled porosity was extended to an apparent impedance parameter for air‐filled porosity. The apparent impedance factor Ωa is about 4 ranging from 0.5 to 6.5 as a function of matric potential. These findings represent significant new progress for estimation of Ωa by an experimental method that can be used for the estimation of snowmelt infiltration. We suggest that the current applied measurement method should be used and further evaluated for a variety of soil types.